Risk factors for chronic liver disease in population of Central India: a case-control study from rural India - Shashank Banait; Shailesh Mohan Badole; Jyoti Jain; Abasaheb Thorat (Egyptian Liver Journal, 2021)
Abstract Background Chronic liver disease (CLD) is one of the leading causes of morbidity and mortality in today’s world. Common risk factors for CLD are alcohol, chronic hepatitis B, chronic hepatitis C, non-alcoholic steatohepatitis (NASH), malnutrition, toxins, and some tropical infections. This case-control study was carried out to determine the risk factors of domestic CLD in a resource-constrained setting in central rural India. A hospital-based matched case-control study was carried out among eligible CLD cases from November 2015 to October 2017. A total of 200 cases and 200 age- and gender-matched community controls were selected using consecutive sampling from tertiary care hospitals from central rural India. Information on socio-demographic, etiological was collected through using a pretested structured questionnaire after obtaining informed written consent. Univariate and multivariate analyses were carried out to find the risk factors associated with CLD. Results The median age of study participant was 58.5 years among the cases. There were 75% male and remaining 25% were female in each case and control group. On multivariate analysis, we found less education, poor socioeconomic status, diabetes mellitus, increased body mass index (BMI), alcohol consumption, and tobacco chewing were significant risk factors for CLD in comparison to controls. However, amount of alcohol, smoking, and occupation were not found to be statistically significant association with CLD. Conclusions The findings showed that in patients with CLD when compared to controls, high alcohol intake, diabetes mellitus, tobacco chewing, central obesity, low education, and low-income group are significant risk factors in our rural population. An initiative needs to be taken to reduce alcohol, and tobacco chewing habits at various levels through awareness campaigns, strict control, and legislation to limit further abuse. Control of blood glucose and reduction of obesity may be important in preventing CLD in our rural community.